SYNTHESIS AND IN VIVO EVALUATION OF SOME NEW PYRAZOL INDOLES, THEIR AZO AND MANNICH SALTS AS ANALGESIC AND ANTI-INFLAMMATORY AGENTS - Archana; Meenakshi Yadav Sakshi Chaudhary
This paper deals with the design, synthesis and biological evaluation of new pyrazolyl indole derivatives including azo compounds and Mannich salts. The work of this research could lead to potentially useful analgesic and anti-inflammatory agents. Utilizing the synthetic route illustrated in Fig. 1, compounds 1 to 30 have been synthesized. All synthesized compounds have been characterized using TLC, elemental analysis for C, H and N and spectral methods involving IR, 1H-NMR, and mass spectroscopy. All tests conducted on standard models in vivo have exhibited excellent analgesic and anti-inflammatory activity, thus suggesting potential therapeutic applications.